OPTIMIZATION MODEL FOR FINANCIAL PERFORMANCE ANALYSIS INDICATORS OF ENTERPRISES - Umarova Shakhnoza, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. This study develops and validates a multi-criteria optimization model for evaluating the financial performance of enterprises across diverse industrial sectors. The model was calibrated against international benchmarks to ensure cross-country validity. The proposed framework provides a replicable, data-driven tool for corporate financial managers, auditors, and policymakers seeking to enhance enterprise competitiveness and financial resilience in emerging-market economies.